A internet como suporte para o jornalismo analítico e investigativo: análise de reportagens da agência pública - Cristianini, Vania Daiana [UNESP] (2015)
This paper aims to discuss the Internet as a space conducive to the development of in-depth reports. The traditional media, often tied to economic and political issues, do not address issues related to collective and social satisfactorily. The emergence of alternative media is important and necessary for the development of investigative journalism, not tied to particular interests. The collective funding or crowdfunding is a financial alternative for the development of journalistic content and the Agência Pública de Reportagem e Jornalismo Investigativo figures as a medium that uses this feature, among others. The analysis of reports produced by the agent allows you to identify aspects of analytical and investigative construction this vast medium that is the Internet